HOW IS THE MENTAL HEALTH OF TIKTOK USERS WHO EXPERIENCE CYBERBULLYING? - Almer Aprillia Edika Putri; Ipah Saripah; Nadia Aulia Nadhirah (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2022)
The rapid development of information technology and technology currently supports an increase in the number of social media users causing the emergence of cyberbullying as a new type of crime. Cyberbullying is a new type of bullying as a result of developments in information technology and technology whose acts of violence are carried out in the cyber world or the internet. Cyberbullying is often experienced by teenagers and most perpetrators of cyberbullying are generally teenagers their age. Victims who experience cyberbullying receive ridicule, insults, threats, or hacking. If this cyberbullying phenomenon is not addressed immediately, it will continue to erode the mental health of adolescents widely, so the attention of many parties is needed in overcoming this problem. Law in Indonesia through Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) has regulated the actions and behavior of cyberbullying. Using the literature review method through a review of various literature, this article describes a study of the concepts, characteristics, and aspects of cyberbullying and its influence on adolescent mental health, especially TikTok users. The conclusion of the study results provides recommendations for the importance of increasing information and communication technology literacy, especially in the use of social media to prevent and minimize the occurrence of cyberbullying.